Breaking bad news and the importance of compassionate palliative care of the infant - William Sessions; Sean Kow; Elizabeth Waldrop; Kayle Stevenson; Ayo Olanrewaju; Thu Tran; Mubariz Naqvi (The Beryl Institute, 2018)
Bad news to parents regarding their infant is information that negatively impacts the parent's feelings and view of the present and/or future. It is implemented in situations with feelings of no hope or those that induce a threat to a parent's mental and physical well-being. The term is difficult to define as it is based on parent's subjective feelings. However, it is important to be aware of the impact of bad news as it can cause severe anguish and stress on the parent's emotional stability. The style of delivering bad news has a significant impact on the physician/parent relationship and the satisfaction of the family upon the healthcare team and palliative care system. In the case of an inevitable death of an infant, the implementation of palliative care follows the delivery of bad news. The strategy of palliative care and the philosophy of communication between the healthcare provider and family unit leave a lasting impression on the parents regarding the care of their infant. Clinicians should strive to educate themselves regarding the art of breaking bad news as well as the approach to palliative care to minimize the suffering and grief of the family in their time of sorrow.